An Engineering Perspective on School Digitalization Application Adoption in Indonesia: A Structural Model Using UTAUT2, TTF, and Trust - Andrean Wijaya; Nilo Legowo (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
This study examines the factors that influence the acceptance of digital school applications in Indonesia against the backdrop of the gap between the number of registered users and active users. Data was obtained from 497 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The research model expands UTAUT2 by adding the variables Task-Technology Fit (TTF) and Trust. The results indicate that Trust significantly influences Usage Behavior (β = 0.403; p < 0.001), while Behavioral Intention is influenced by Social Influence (β = 0.135; p = 0.016), Facilitating Conditions (β = 0.287; p < 0.001), and TTF (β = 0.292; p = 0.005). Behavioral Intention further serves as the primary predictor of Use Behavior (β = 0.495; p < 0.001). The R² values of 0.788 for Behavioral Intention and 0.834 for Use Behavior indicate strong explanatory power. These findings emphasize the importance of building trust, infrastructure support, and technological suitability to enhance user engagement, while also providing practical insights for app developers and education policymakers.